WHAT FACTORS CAUSE DIFFERENCES IN ECONOMIC GROWTH IN NORTH BANTEN AND SOUTH BANTEN? - Hutagaol, Manuntun Parulian; Qaedi, Muhammad Redo; Hayat, Mohsina (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study examines the factors contributing to the economic growth imbalance between North and South Banten. Using panel data from six regencies and cities in North Banten and two regencies in South Banten for the period 2010-2020, the research employs both descriptive qualitative analysis and quantitative regression analysis. The findings reveal that in North Banten, factors such as foreign direct investment (FDI), domestic direct investment (DDI), electricity, human development index (HDI), industrial sector, and service sector positively and significantly influence economic growth. However, road infrastructure and the agriculture sector show no significant effect. In contrast, in South Banten, only the agriculture and service sectors have a positive significant impact, while FDI, DDI, road infrastructure, electricity, HDI, and the industrial sector do not significantly affect economic growth. To address the economic growth imbalance in Banten, policies should focus on enhancing investment interest, improving infrastructure, developing human resources, and maximizing key production sectors.